Management of the postpartum ovarian and partial cava inferior vein thrombosis - S. Dikić; S. Dragojević; L. Nejković; J. Štulić; A. Juri šić; D. Radojičić; A. Diki ć; Dj Radak (IMR Press, 2020)
Objective: Postpartum ovarian vein thrombosis (POVT) is a rare but very dangerous complication with possible lethal outcome. Here the authors present a case of POVT with propagation in cava inferior vein, which was diagnosed fourth day after delivery by cesarean section. Case Report: A 27-year-old female with fever complained of pain in the area of the right side of the abdomen, in the ileocecal region three days after premature delivery by caesarean section. Right ovarian venous thrombosis and partial cava inferior vein thrombosis was demonstrated on sonography and confirmed with computed tomography. She was treated with antibiotics and anticoagulation therapy with good response. Conclusion: If women after delivery have an elevated temperature with abdominal pain and leukocytosis in laboratory analyzes, it is always necessary to think of the POVT. Early recognition and therapy are crucial.